Pendampingan Pemanfaatan Teknologi dalam Desain Pembelajaran Daring Bagi Guru Pada Masa Pandemi Covid-19 - Mohammad Asrori; Agus Mukti Wibowo; Imroatul Hayyu Erfantinni; Dessy Putri Wahyuningtyas (Departement of Mathematics Education, 2023)
This global pandemic situation demands various changes in the world of education, including in the teaching and learning process which must be done online through online learning media. Many teachers have difficulties in this regard, one of which is the MGMP PAI SMK Blitar Regency. Therefore, this research will assist in the use of various applications that can help online learning at the MGMP PAI SMK in Blitar Regency. In this research-based service, the researcher es the Participatory Action Research approach, starting with planning; action; evaluation; reflection. This research is used for development solutions, in this case concerning Digital Application-Based Learning Service Development solutions. The activities carried out began with a need assessment in the form of an FGD between the Research Team and the MGMP PAI SMK Blitar Regency and the Ministry of Religion of Blitar Regency. The results of this research-based dedication conclude the importance of organizing training and mentoring in the use of online learning technology to meet the needs of PAI SMK teachers throughout Blitar Regency. The materials that enforce training and mentoring include: teleconference applications, learning video applications, and online learning evaluation applications. Then the team conducted a periodic mentoring evaluation process by forming a telegram group, WA group, and google classroom.